Penerapan Metode Teams Game Tournament untuk Meningkatkan Keaktifan Siswa Kelas 1 dalam Pembelajaran Matematika - Desy Suci Ramadayanti; Nur Qomariah; Hairun Nisa (Mataram University, 2026)
This study is motivated by the low level of student activeness in mathematics learning, as indicated by limited participation in asking questions, responding, and engaging in discussions during the learning process. One potential solution to address this issue is the implementation of the Teams Game Tournament (TGT) method. This study aims to enhance student activeness in mathematics learning through the application of the TGT method. The research employed a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of two meetings and four stages: planning, implementation, observation, and reflection. The research subjects were 30 fifth-grade students. Data were collected through observation, questionnaires, and documentation. The results indicate an improvement in student activeness, increasing from 62% in Cycle I to 86% in Cycle II. It can therefore be concluded that the implementation of the Teams Game Tournament method effectively improves student activeness in mathematics learning.